2000
DOI: 10.1002/1096-8628(20001204)96:6<744::aid-ajmg9>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of CAG repeats at theKCNN3 locus in Indian patients with bipolar disorder and schizophrenia

Abstract: Bipolar affective disorder and schizophrenia are severe behavioral disorders with a lifetime risk of approximately 1% in the population worldwide. There is evidence that these diseases may manifest the phenomenon of anticipation similar to that seen in diseases caused by trinucleotide repeat expansions. A recent report has implicated a potassium channel-coding gene, KCNN3, which contains a polymorphic CAG repeat in its coding region, in schizophrenia and bipolar disorder. We have tried to confirm these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…The values which are indicated in parentheses are P-values which were obtained from chi-square analysis when comparison was between the present study and the other studies using MedCalc 7.6.0.0. Table 4: Clinical details of the patients with lower repeats than the normal range at SCA 8 locus At SCA8 locus repeats varied from 18-33 with 90% of the alleles having less than 27 repeats in northern Indian population [22] and in the present study repeats varied from 16-37 (Figure 2) with 44% of the alleles having >27 repeats which indicates that greater repeat size at SCA 8 locus is more in southern population of India. The frequencies of large normal alleles at SCA 8 locus were quite high when compared with other populations (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…The values which are indicated in parentheses are P-values which were obtained from chi-square analysis when comparison was between the present study and the other studies using MedCalc 7.6.0.0. Table 4: Clinical details of the patients with lower repeats than the normal range at SCA 8 locus At SCA8 locus repeats varied from 18-33 with 90% of the alleles having less than 27 repeats in northern Indian population [22] and in the present study repeats varied from 16-37 (Figure 2) with 44% of the alleles having >27 repeats which indicates that greater repeat size at SCA 8 locus is more in southern population of India. The frequencies of large normal alleles at SCA 8 locus were quite high when compared with other populations (Table 3).…”
Section: Discussionsupporting
confidence: 49%
“…Calcium channels have been previously implicated in bipolar disorder and schizophrenia. 27 The gene which encodes synaptogyrin 1, a protein which is involved in presynaptic vesicle formation in neurons, 36 is also found within 2 Mb of the 22CH3 locus. While this manuscript was under review, Mirnics et al reported altered levels of synaptoMolecular Psychiatry gyrin 1 in the prefrontal cortex of some of the patients suffering from schizophrenia using microarray analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the patients and controls have been used in earlier published studies. 26,27 The number of patient and control samples used for the individual loci are given in Table 1.…”
Section: Selection Of Patients and Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin studies have also been used in biometric studies to determine the most likely disease model. Cardno and colleagues performed such an analysis on pooled twin data and found that a model containing additive genetic and environmental effects gave the best fit, with a heritability of 83% (95% CI [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and specific environmental effects of 17% (95% CI 10-26) [13]. Discordant MZ twin studies have also shown that the children of both affected and unaffected MZ twins have similar risks of schizophrenia-like psychosis [14].…”
Section: Evidence For a Genetic Basismentioning
confidence: 99%